Strategi Pengembangan Usaha Mikro Kecil dan Menengah (UMKM) Sepatu Melalui Peningkatan Kualitas Sumber Daya Manusia di kecamatan Kesamben Jombang - Lailatus Sa’adah; Nisa Candra Mutammimah (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
This research aims to analyze the differences in development strategies in small and medium micro-enterprises shoes through improving the quality of human resources in Kesamben Jombang district. The method used in this research is a qualitative method with data collection through observation, interviews, and documentation involving directly to 2 owners of Micro, Small and Medium Enterprises shoes in Kesamben sub-district. Data analysis techniques include data reduction, data presentation, and conclusion drawing. Data validity testing is done by testing credibility (internal validation), transferability (external validation), dependability, and confirmability (objectivity). The result of this research is that the improvement of human resources carried out by the Mekar Abi Mulya micro, small and medium enterprises is very helpful for the owner in business continuity and business development, so that the company survives until now. In improving the quality of employees, UD Abi Mulya micro, small and medium enterprises apply aspects in improving the quality of employees, namely: Training, knowledge, experience, personality, and productivity. Meanwhile, UD Riaji in improving the quality of employees is applying aspects: Training, knowledge, personality, and productivity.